Incidence and prevalence of psoriasis in multiethnic Johor Bahru, Malaysia: a population‐based cohort study using electronic health data routinely captured in the Teleprimary Care (TPC®) clinical information system from 2010 to 2020. (8th August 2022) - Choon, Siew Eng; Wright, Alison K.; Griffiths, Christopher E.M.; Tey, Kwee Eng; Wong, Kit Wan; Lee, Yoong Wei; Suvelayutnan, Ushananthiny; Mariapun, Jeevitha; Ashcroft, Darren M.; ,
Summary: Background: There are no population‐based epidemiological data on psoriasis in Southeast Asia, including Malaysia. Objectives: To determine the incidence and prevalence of psoriasis over 11 years in multiethnic Johor Bahru, Malaysia. Methods: A population‐based cohort study was made using the Teleprimary Care database between January 2010 and December 2020. Cases of psoriasis, identified by ICD‐10 diagnostic codes, were validated by dermatologists. Annual prevalence and incidence were estimated and stratified by age, sex and ethnicity. Results: We identified 3932 people with dermatologist‐confirmed psoriasis, including 1830 incident cases, among 1 164 724 Malaysians, yielding an 11‐year prevalence of 0·34% [95% confidence interval (CI) 0·33–0·35] and incidence of 34·2 per 100 000 person‐years (95% CI 32·6–35·8). Rates were higher in Indian patients; the prevalences were 0·54% (0·50–0·58) in Indian, 0·38% (0·36–0·40) in Chinese and 0·29% (0·28–0·30) in Malay patients, and the respective incidences per 100 000 person‐years were 52·5 (47·3–57·7), 38·0 (34·1–41·8) and 30·0 (28·2–31·8). Rates were higher in males; the prevalence was 0·39% (0·37–0·41) in males and 0·29% (0·27–0·30) in females, and the respective incidences per 100 000 person‐years were 40·7 (38·2–43·2) and 28·3 (26·4–30·3). Between 2010 and 2020, annual psoriasis prevalence and incidence increased steadily from 0·27% to 0·51% and from 27·8 to 60·9 per 100 000 person‐years, respectively. Annual rates were consistently higher in male and Indian patients. Overall, psoriasis was significantly more common in males than females [odds ratio (OR) 1·37, 95% CI 1·29–1·46] and in Indian and Chinese patients vs. Malay (OR 1·85, 1·71–2·01 and OR 1·30, 1·20–1·41, respectively). Prevalence increased with age, with the highest rates in the groups aged 50–59 and 60–69 years at 0·67% and 0·66%, respectively. A modest bimodal trend in age of psoriasis onset was observed, with first and second peaks at 20–29 and 50–59 years. Disease onset was significantly earlier in females than males [mean (SD) 36·8 (17·3) vs. 42·0 (17·2) years, P  < 0·001] and in Malay vs. Indian and Chinese patients [mean (SD): Malay 36·4 (17·5), Indian 40·8 (15·2), Chinese 47·4 (16·9) years, P  < 0·001]. Conclusions: We found that psoriasis incidence and prevalence are increasing and varied by age, sex and ethnicity. Our findings should help inform healthcare planning and management for patients with psoriasis in Malaysia. What is already known about this topic? The incidence and prevalence of psoriasis are generally lower in Asian populations and children. There is a lack of agreement on sex‐specific differences in psoriasis incidence and prevalence. There has been no population‐based study on the incidence and prevalence of psoriasis in Southeast Asia, including Malaysia. There is no information on differences in psoriasis prevalence and incidence by sex, age and ethnicity in Malaysia. What does this study add? Psoriasis incidence and prevalence are increasing in the multiethnic population of Johor Bahru, Malaysia. Incidence and prevalence rates were higher in male than female patients and were consistently highest among Indian patients, followed by Chinese and Malay. A modest bimodality in the age of psoriasis onset was observed among the groups aged 20–29 and 50–59 years. Psoriasis onset was significantly later in male than female patients and in Chinese vs. Indian and Malay patients. Abstract : Between 2010 and 2020, annual psoriasis prevalence and incidence in Johor Bahru, Malaysia, increased steadily from 0.27% to 0.51% and 27.8 to 60.9/100, 000 person‐years, respectively. Annual rates were consistently higher in males than females and among Indians, followed by Chinese and Malays. Overall, psoriasis was significantly more common in males than females and in Indians and Chinese than in Malays. Prevalence increased with advancing age, with the highest rates in the 50–59 and 60–69 age groups at 0.67% and 0.66%, respectively. A modest bimodal trend in the age of psoriasis onset was observed with first and second peaks at 20–29 and 50–59 years of age, respectively. Disease onset was significantly earlier in females than in males and in Malays than in Indians and Chinese. Plain language summary available online